Effects of dietary selenium deficiency and supplementation on liver in grazing sheep: insights from transcriptomic and metabolomic analysis - Jin, Xiwei; Meng, Lingbo; Qi, Zhi; Mi, Lan (Frontiers in Veterinary Science, 2024)
Background: Mineral elements play a crucial role in supporting the life activities and physiological functions of animals. However, numerous studies have revealed that in some geographical areas and certain grazing situations, grazing livestock frequently suffers from mineral element deficiencies due to the loss of mineral elements from grassland forages, such as selenium (Se). To shed fresh light on this issue, this study aims to investigate the impact of dietary Se deficiency and supplementation on the liver of grazing sheep in these challenging conditions.Method: This study involved 28 grazing Mongolian Wu Ranke sheep with an average body weight of about 32.20 ± 0.37 kg, which were divided into the Se treatment group and the control group. The Se treatment group was fed with the low-Se diet for 60 days and then continued to be fed with the high-Se diet for 41 days. The liver concentration of minerals, transcriptomic analysis, and untargeted metabolomic analysis were conducted to assess the impact of Se deficiency and supplementation on the liver of grazing sheep.Results: Dietary Se deficiency and supplementation significantly reduced and elevated liver concentration of Se, respectively (p < 0.05). Gene functional enrichment analysis suggested that dietary Se deficiency might impair protein synthesis efficiency, while Se supplementation was found to enhance liver protein synthesis in grazing sheep. AGAP1, ERN1, MAL2, NFIC, and RERG were identified as critical genes through the weighted gene correlation network analysis, the quantitative real-time polymerase chain reaction, and the receiver operating characteristic curve validation that could potentially serve as biomarkers. Metabolomics analysis revealed that dietary Se deficiency significantly reduced the abundance of metabolites such as 5-hydroxytryptamine, while dietary Se supplementation significantly elevated the abundance of metabolites such as 5-hydroxytryptophan (p < 0.05).Integrative analysis of the transcriptome and metabolome revealed that dietary Se deficiency led to reduced hepatic antioxidant and anti-inflammatory capacity, whereas Se supplementation increased the hepatic antioxidant and anti-inflammatory capacity in grazing Wu Ranke sheep. These findings provide new insights into the effects of dietary Se deficiency and supplementation on the liver of grazing sheep, potentially leading to improved overall health and well-being of grazing livestock.